Diagnosis of Brain Death in a Multidisciplinary Hospital - A. I. Gritsan; N. Y. Dovbysh; E. E. Korchagin (Общая реаниматология, 2024)
Brain death diagnosis (BDD) remains a challenge for anesthesiologists and intensive care physicians despite existing regulatory frameworks.   Objective. To evaluate the frequency of BDD procedure and identify factors limiting its implementation in a multidisciplinary hospital setting.   Materials and Methods. A single-center retrospective study was conducted including 698 patients by total sampling. Of these, 98 (14 %) had brain injury and were selected for further analysis. From this cohort, patients who died within 15 days of hospital admission (N = 61) were identified. A subgroup of patients with a Glasgow Coma Scale (GCS) score of 3–5 was then selected (N = 38). For comparison, a literature search was performed in PubMed using the query «brain death criteria» and in eLibrary.ru using the keywords «brain death diagnosis».   Results. BDD was initiated in 12 (31.6 %) cases within the GCS 3–5 subgroup, with brain death confirmed in 8 (21.1 %) patients, including 5 (63 %) women and 3 (37 %) men. Complete BDD procedures were performedin 6 (75 %) patients with non-traumatic intracerebral hemorrhage (ICH), 1 with non-traumatic subarachnoid hemorrhageь (SAH), and 1 with traumatic brain injury (TBI) (12.5 % each). The median patient age was 59 [43; 65] years, the median GCS score was 3 [3; 3], and the median FOUR score was 0 [0; 0]. Median hospital length of stay was 1.5 [1; 2.5] days, and median intensive care unit (ICU) stay was 1 [1; 2] day.   Conclusion. Insufficient pupil diameter (5 mm) is a limiting factor for the performance of BDD procedures in grade III coma patients.